Analysis of study choice motives and study satisfaction as an instrument of study quality assurance - Liucija Urbonienė (Taikomieji Moksliniai Tyrimai, 2022)
The article analyses the modern scientific concepts of students' satisfaction with studies and the motives for choosing studies. Based on the results of the questionnaire survey are analysed the motives for choosing the studies by the part-time first-year students of the groups of study fields of Social Sciences and Business and Public Administration of the Faculty of Business and Technologies of Šiauliai State University of Applied Sciences, and the students’ satisfaction with the studies. Based on the analysis of scientific literature and a questionnaire survey, the aim was to determine what motives encourage students to choose to study at Šiauliai State University of Applied Sciences, to identify the key criteria that determine students’ satisfaction or dissatisfaction with studies in terms of the quality of studies. Keywords: quality of studies, choice of studies, study program, satisfaction with studies.